The association of patient safety culture with intent to leave among Jordanian nurses: a cross-sectional study - Islam Oweidat; Ghada Abu Shosha; Kawther Dmaidi; Abdulqadir J. Nashwan (BMC, 2023)
Abstract Background The existence of patient safety culture is crucial for healthcare providers' retention, particularly for nurses. Patient safety culture is getting more attention from healthcare organizations worldwide, and Jordan is no exception. Nurses' satisfaction and retention are paramount to providing safe, high-quality patient care. Purpose To investigate the relationship between patient safety culture and intent to leave among Jordanian nurses. Methods A descriptive cross-sectional design was used. A sample of 220 nurses was selected through convenience sampling from one governmental and one private hospital in Amman. The patient safety culture survey and anticipated turnover scale were used to collect data. Descriptive statistics and Pearson r correlation were used to answer the research questions. Results The findings showed that nurses had 49.2% positive scores for patient safety. Teamwork (65.3%) and handoff and exchange of information (62% each) had the highest scores, while staffing and workplace (38.1%) and response to error (26.6%) had the lowest. Moreover, nurses had strong intentions to leave their jobs (M = 3.98). A moderately significant but not highly negative relationship existed between patient safety culture and intent to leave (r = -0.32, p = 0.015). Conclusions There are opportunities to improve patient safety culture, satisfaction, and nurse retention in Jordanian hospitals by implementing several recommendations, such as ensuring better staffing patterns and increasing staff motivation by utilizing various available methods.